Pengaruh Motivasi Kerja, Lingkungan kerja, dan Beban Kerja terhadap Kinerja Karyawan di Departemen Produksi Plywood pada PT. Kayu Lapis Indonesia - Dwi Indah Agustyaningrum; Sri Isnowati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study is to identify the influence of work motivation, work environment, and workload on the performance of employees of the plywood production department at PT Kayu Lapis Indonesia. The findings of this study are expected to be able to strengthen the empirical study literature that has been previously stated. The sampling technique used in this study was purposive sampling. The number of samples that met the criteria was 93 respondents. The data used is primary data by collecting data through distributing questionnaires and interviews to employees of the plywood production department at PT Kayu Lapis Indonesia. The data analysis method uses multiple linear regression with the SPSS version 26. The results of the test show that work motivation partially had a positive and significant effect on employee performance, the work environment partially had a positive and significant effect on employee performance, and workload partially had a negative and significant effect on employee performance. Work motivation, work environment, and workload variables simultaneously have a significant effect on employee performance. The coefficient of determination of employee performance in this test is 65.6%, which shows the contribution of work motivation variables, work environment, and workload can affect employee performance.